MODEL TRAINING NEEDS ANALYSIS UNTUK MEMBENTUK PERILAKU INOVATIF SDM INDUSTRI KECIL SEPATU DI JAWA TIMUR - Anita Kristina (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
Market Extension and product inovation every moment is conducted by industry, this matter needs the better skill from the production to increase performance of innovative and understanding to new product.The aim of this research is to compile the model of Training Needs Analysis ( TNA) which is needed to identify the training requirement in order to overcome theworker competence in innovative performance, this is in the small industry. TNA is very important because TNA assists to find whether deficiencies of innovative performance can be improved with the training. The result of this research indicates that the innovative behavior is fundamental problem and become the main problem  which must be finished with training. The  result of this study indicates that TNA is  shown in  a model of concept of  a system that is consist of input, process, and output. Process of analysis finds the  discrepancy and cause from the problem of skill inovative. The output of this model  is the training needs and non training needs.